Assessing digital literacy among aborigines: a case of the Semai tribe in Kampung Bukit Terang, Kampar, Perak / Rugayah Hj. Hashim … [et al.] - Hj. Hashim, Rugayah (Research Management Institute (RMI), 2012)
The purpose of this research was to assess the level of computer literacy among the indigenous Semai tribe in Kampung Bukit Terang, Kampar, Perak, Malaysia. Forty questionnaires were distributed to the respondents who were conveniently available at the time of the visit. With the help of forty university students, 39 (97.5%) completed sets were returned. The descriptive analyses showed that 30.8% of the respondents have never attended school and are considered illiterate. Only 5.2% are computer literate and this finding suggests that the digital divide is wide among this minority group, thus, the argument on digital exclusion is substantiated. The implication of the research provides justification for policy analysis on technology for social inclusion. It then draws on the political environment that has resulted in this tribe being marginalized and the need to promote access for social inclusion and citizen development.